(NfIZIKA ION(B-(NIONNYH I \LEKTRON(B-(NIONNYH STOLKNOWENIJ (B/s - (NdALGARNO(B, (Na(B.s; (NpOST(B, (Nd(B.(Ne(B.s; (NgUBERMAN(B, (Ns(B.(Nl(B.s; (N~IBISOW(B, (Nm(B.(Ni(B.s; (NbRUJAR(B, (Nf(B.s; (NmAK(B-(NgOU\NA(B, (NdV(B.s; (NfIRSOW(B, (NoLEG bORISOWI^s ((NmOSKWA (B:s (NmIR(B,s, 1986)
(NpREDM(B. (NUKAZ(B.: (NS(B. 427-429s
(NbIBLIOGR(B. (NW KONCE GLAWs
Keywords: (NaTOMNYE STOLKNOWENIQs; (NpLAZMA WYSOKOTEMPERATURNAQs